Analysis of volatiles and 18S rRNA gene of Haplophyllum canaliculatum in in vitro cultures - M. Nikbakht; A. Gholami; M.H. Morowvat; Y. Ghasemi; A. Mohagheghzadeh (Iranian Society of Pharmacognosy, 2016)
Background and objectives:  Haplophyllum canaliculatum isan endemicand endangeredIranian plant from Rutaceae family. The object of this work was to study the volatile production in established shoot and callus cultures of Haplophyllum canaliculatum as well as isolation, identification and sequencing of 18S rRNA gene from callus culture. Methods: Shoot and callus cultures of H. canaliculatum were established from seedlings and shoot cultures, respectively. Both cultures were transferred to MS medium supplemented with α-naphthalene acetic acid (α-NAA), 2,4-dichlorophenoxyacetic acid (2,4-D) and kinetin (Kn). Volatiles from fresh callus and shoot cultures were extracted and analyzed by GC/MS. For 18S rRNA gene study, DNA content was extracted using PCR procedure. The study of sequence similarities was performed using NCBI database and GeneDoc software. Results: GC/MS analysis of H. canaliculatum showed that shoot cultures mainly contained piperitone (10.92%), and β-caryophyllene (12.67%) in addition to three alkaloids, while calli cultures of H. canaliculatum mainly contained methylated salicylate (31.55%), alkane structures like tetradecane (24.31%) and hexadecane (12.95%). Gene analysis showed 98% homology with certain species of Rutaceae, Meliaceae, Simaroubaceae, Burseraceae and Cneoraceae. Conclusions: Our results showed that the hydrocarbon in addition to methyl salicylate biosynthetic pathway in calli cultures and terpene as well as alkaloid biosynthetic pathway were active in H. canaliculatum shoot cultures. Moreover, the obtained sequences could be used as a "DNA barcoding" tool through the concept of one sequence one species for the practical identification of this species.